ðŸ‘‰ Try now NerdPal! Our new math app on iOS and Android

# Solve the rational equation $\frac{36\left(x^2-1\right)}{\left(x^2+3\right)^3}=0$

Go!
Symbolic mode
Text mode
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

##  Final answer to the problem

$x=1,\:x=-1$
Got another answer? Verify it here!

##  Step-by-step Solution 

How should I solve this problem?

• Choose an option
• Solve for x
• Find the derivative using the definition
• Solve by quadratic formula (general formula)
• Simplify
• Find the integral
• Find the derivative
• Factor
• Factor by completing the square
• Find the roots
Can't find a method? Tell us so we can add it.
1

Multiply both sides of the equation by $\left(x^2+3\right)^3$

$36\left(x^2-1\right)=0$

Learn how to solve problems step by step online.

$36\left(x^2-1\right)=0$

Learn how to solve problems step by step online. Solve the rational equation (36(x^2-1))/((x^2+3)^3)=0. Multiply both sides of the equation by \left(x^2+3\right)^3. Solve the product 36\left(x^2-1\right). We need to isolate the dependent variable x, we can do that by simultaneously subtracting -36 from both sides of the equation. Divide both sides of the equation by 36.

##  Final answer to the problem

$x=1,\:x=-1$

##  Explore different ways to solve this problem

Solving a math problem using different methods is important because it enhances understanding, encourages critical thinking, allows for multiple solutions, and develops problem-solving strategies. Read more

SnapXam A2

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch